The The Role of Fishermen's Wives in Increasing Household Income in Central Tapanuli Regency, North Sumatera: Peran Istri Nelayan dalam Meningkatkan Pendapatan Rumahtangga di Kabupaten Tapanuli Tengah, Sumatera Utara - Tirta Anugerah; Alfansuri, Muhammad Fikri; Zulkarnain, Umar; Harahap, Husnul Yaqin; Siburian, Juliana Pebrina (Metafora: Education, Social Sciences and Humanities Journal, 2025)
The purpose of this study is to identify the activities of fishermen's wives in increasing household income, to determine the contribution of fishermen's wives' income to the total household income, and to determine the relationship between wives' income and household welfare. In collecting data, this study used a survey method for 36 fishermen's wives. This study shows that the activities carried out by fishermen's wives are selling fish around, opening a food stall, raising goats, and being a housewife. The value of the contribution of fishermen's wives to the total household income is 37.30%, where the average income of fishermen's wives per month is Rp. 808,333, which they feel is not enough to meet household needs. The results of the simple correlation analysis (Pearson correlation) test of the wife's income (X) and family welfare (Y) variables obtained a value of 0.443 with a moderate category.